2012
DOI: 10.3324/haematol.2011.055285
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput molecular diagnosis of von Willebrand disease by next generation sequencing methods

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nregions and flanking intronic regions of VWF (~10 Kb) are included ( Figure 1A). Normalization of amplicons was carried out by gel quantification performed with ImageJ (Version 1.43u), a public domain Java image processing program (http://rsbweb.nih.gov/ij/). By taking a sample with a known concentration as the control, it was possible to extrapolate the concentration of each sample to create a normalized pool of the 47 PCR products in one tube. This pooling proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…rs7962217 was associated with higher FVIII levels whereas rs41276738 was associated with lower levels and had an effect size similar to that of the strongest genetic predictor of FVIII levels, the O-deletion tagging SNP (rs657152). rs41276738 has been reported in patients with von Willebrand disease type 1 34,35 and type 2N, [36][37][38][39][40][41][42][43] but the association with vWF levels did not reach exome-wide significance, although its direction was consistent with the direction of effects on FVIII. The STAB2 variant rs141041254 was associated with higher plasma levels of both FVIII and vWF.…”
Section: Fviii and Vwfmentioning
confidence: 53%
See 1 more Smart Citation
“…rs7962217 was associated with higher FVIII levels whereas rs41276738 was associated with lower levels and had an effect size similar to that of the strongest genetic predictor of FVIII levels, the O-deletion tagging SNP (rs657152). rs41276738 has been reported in patients with von Willebrand disease type 1 34,35 and type 2N, [36][37][38][39][40][41][42][43] but the association with vWF levels did not reach exome-wide significance, although its direction was consistent with the direction of effects on FVIII. The STAB2 variant rs141041254 was associated with higher plasma levels of both FVIII and vWF.…”
Section: Fviii and Vwfmentioning
confidence: 53%
“…Some of the variants have been found in patients with diseases related to blood clotting, which suggests that these genes and their uncommon and rare genetic variation may play a role in a clinical phenotype. [26][27][28][32][33][34][35][36][37][38][39][40][41][42][43] The distribution of the phenotypes within our research populations were within the extremes of a clinically activity, and 2% to 297% antigen; FVIII: 14% to 500% activity; and vWF: 2% to 374% antigen). Furthermore, the magnitude of difference in the phenotype associated with the variant was mostly modest, although some were larger and were associated with a change equivalent to half the size of the estimated population mean for the phenotype of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively few patients achieve deep and sustainable responses that would render them eligible for a stopping study similar to STIM or TWISTER. Milojkovic et al 8 over time. But we are left with the fact that after 14 years of imatinib therapy, less than 5% of patients have been able to durably discontinue therapy.…”
mentioning
confidence: 98%
“…These authors used a modified version of the NGS method previously reported by Corrales et al [20] and the reliability of this NGS approach has already been confirmed by Fidalgo and colleagues [22] on a cohort of Portuguese VWD patients. In Figure 2 a schematic representation of this NGS procedure is summarized.…”
Section: Next Generation Sequence (Ngs) Analysismentioning
confidence: 99%
“…Newly developed genetic methods such as NGS are becoming faster and progressively cheaper, allowing wider study of VWF mutations at a very reasonable cost [20]. NGS enables investigation of the entire VWF coding region in a short time and therefore this approach is better suited to investigate VWD types 1 and 3 variants.…”
Section: Next Generation Sequence (Ngs) Analysismentioning
confidence: 99%